Development of a quantitative PCR assay for measurement of trichechid herpesvirus 1 load in the Florida manatee (Trichechus manatus latirostris). (July 2017) - Ferrante, Jason A.; Cortés-Hinojosa, Galaxia; Archer, Linda L.; Wellehan, James F. X.
Trichechid herpesvirus 1 (TrHV-1) is currently the only known herpesvirus in any sirenian. We hypothesized that stress may lead to recrudescence of TrHV-1 in manatees, thus making TrHV-1 a potential biomarker of stress. We optimized and validated a TrHV-1 real-time quantitative probe hybridization PCR (qPCR) assay that was used to quantify TrHV-1 in manatee peripheral blood mononuclear cells (PBMCs). Average baseline TrHV-1 loads in a clinically healthy wild Florida manatee ( Trichechus manatus latirostris ) population ( n = 42) were 40.9 ± SD 21.2 copies/100 ng DNA; 19 of 42 manatees were positive. TrHV-1 loads were significantly different between the 2 field seasons ( p < 0.025). This optimized and validated qPCR assay may be used as a tool for further research into TrHV-1 in Florida manatees.